2005
DOI: 10.1111/j.1365-2265.2005.02214.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective screening for coeliac disease in patients with Graves’ hyperthyroidism using anti‐gliadin and tissue transglutaminase antibodies

Abstract: Screening 111 consecutive patients with Graves' hyperthyroidism revealed AGA in 14%, anti-tTG in 2% and IgA deficiency in 3%. Two patients were known to have CD. Screening detected three new cases. The prevalence of CD in patients with Graves' hyperthyroidism was 4.5% as compared with 0.9% in matched healthy controls. Routine screening for CD should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 29 publications
(39 reference statements)
2
41
1
4
Order By: Relevance
“…This is somewhat lower than recent (smaller) studies which reported percentages between 2.7 and 4.8 (20)(21)(22)(23). We ruled out IgA-deficiency since Em and TTG test are an IgA-class test.…”
Section: Graves'contrasting
confidence: 40%
“…This is somewhat lower than recent (smaller) studies which reported percentages between 2.7 and 4.8 (20)(21)(22)(23). We ruled out IgA-deficiency since Em and TTG test are an IgA-class test.…”
Section: Graves'contrasting
confidence: 40%
“…Further supportive of a link between these three immune-mediated conditions is the higher prevalence of CD in both T1D and ATD (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…However, the real pathogenetic link between the immune response and the pathogenesis of CD is still foggy, despite the hundreds of reports (now repetitive) describing the reliability of the determination of transglutaminase autoimmunity in diagnosis of CD. In addition, it is emerging that antitransglutaminase antibodies are also raised in a few other autoimmune conditions, including heart failure, thyroid and articular diseases (Ch'ng et al 2005;Sane 2008). …”
Section: The Years Of Diseasementioning
confidence: 99%